Who Takes You to the Dance? How Partners’ Institutional Logics Influence Innovation in Young Firms - Pahnke, Emily Cox; Katila, Riitta; Eisenhardt, Kathleen M. (Administrative Science Quarterly, 2015)
Drawing on institutional theory, we examine how the institutional logics—taken-for granted norms, structures, and practices—of different types of funding partners influence young firms and their search for innovations. We test our hypotheses in a longitudinal study of a complete population of ventures in the minimally invasive surgical device industry in the U.S., supplemented by interviews with industry informants. We find that types of funding partners vary significantly from one another: they all provide resources, but their institutional logics differ. Venture capitalists (VCs) pick young firms with significant patented technologies and help firms launch products, and high-status VCs strengthen both the patenting and product innovations of young firms. Corporate venture capitalists and government agencies also select patent-intensive firms but are less effective than VCs in helping ventures during the relationship because, though these partners often have impressive technical and commercial resources for innovation, their institutional logics constrain how effectively young firms can access their resources. Relative to other types of funding partners, VCs have a closer advisor relationship with the venture; greater power, influence, and access to resources; better-paced and more-motivating milestones; and better understanding of the commercialization process. Our results extend the institutional logics literature to interorganizational relationships and suggest that the choice among types of funding partners may have unanticipated effects on firms’ innovation beyond the financial resources gained through the relationship.